An analysis of the economic feasibility of a pistachio processing facility - Kusmak, Michael T. (Kansas State University, 2008)
The economic feasibility of adding a pistachio roasting facility to the current operations of Tularosa Pistachio Groves (TG) was examined. A facility that roasts and processes 200,000 pounds of pistachio nuts was found to be the most economically viable for the available product grown by (TG) and other small growers in this area. This size facility optimizes the production capacity of the equipment needed for a small grower/processor and fully utilizes a fulltime skilled labor pool needed for the operation. Lower production levels utilize the same equipment on an intermittent schedule. Although operating costs are less when processing fewer pistachio nuts, the negative cash flows during the early period of the project are significant and make the lower production levels less financially viable. The primary reason the lower production quantities are less attractive is because the initial capital investment produced lower cash incomes in the early years of operation. Additional cash is needed for the operation costs, and principal and interest payments. Achieving maximum production to utilize the capacity of the facility sooner makes the project more financially feasible.
Keywords: Pistachio; Cash flow; Simulation; Agribusiness; Capitol Budgeting; Risk Analysis; Agriculture, General (0473); Agriculture, Plant Culture (0479); Economics, Agricultural (0503)